A hands-on approach to demonstrating active noise cancelling. Issue 1 (December 2020) - Coandă, P; Avram, M; Comeagă, D
Abstract: As noise pollution has become an increasingly major factor in the quality of urban life, noise cancelling methods started to be a relevant option for everyday life. Starting from the first active noise cancelling headphones build for aircraft industry in order to facilitate communication between pilots, in the last decade, active noise cancelling products have become more and more relevant. Factories, military and lately, civil usage of active noise cancelling technology transformed this industry and made it widely available. The purpose of this paper is to demonstrate a practical way of active noise cancelling using LabVIEW. Two sound waves are guided through a cylindrical conduit and at a given position, by modifying the phase and amplitudes between the two signals, an amplitude close to zero is expected.